Silver based hybrid nanocomposite: A novel antibacterial material for water cleansing. (15th February 2021) - Abdulla, Noufal Komby; Siddiqui, Sharf Ilahi; Fatima, Bushra; Sultana, Razia; Tara, Nusrat; Hashmi, Athar Adil; Ahmad, Razi; Mohsin, Mohd; Nirala, Ranjeet Kumar; Linh, Nguyen Thuy; Bach, Quang-Vu; Chaudhry, Saif Ali
Abstract: The synthesis, characterization, adsorption, and antibacterial activities of silver-based hybrid nanocomposite, Ag/Ag2 O/ZrO2 /GL, is being reported herein. The composite was synthesized by incorporating silver and zirconium oxides nanoparticles into organic framework derived from abundant fruit bearing medicinal plant leaves of Psidium guajava. The prepared composite was characterized by employing several spectroscopic and microscopic techniques to establish the morphology, and the functional sites at the surface. It was investigated for the adsorption of methylene blue dye from water which revealed that 2.0 g L −1 of Ag/Ag2 O/ZrO2 /GL could clean solution having 10–60 mg L −1 concentrations in 120 min contact time. The process of dye adsorption was found to be endothermic and spontaneous on the basis of thermodynamic parameters. The investigation further revealed that the Freundlich isotherm explained adsorption data satisfactorily. The reaction followed pseudo-second order kinetics and which was controlled by intraparticle diffusion step. The thermodynamics, isothermal, and kinetics studies suggest that combination of electrostatic and physical adsorption was responsible for the methylene blue removal from water by Ag/Ag2 O/ZrO2 /GL. The equilibrium partition coefficient and adsorption capacity were 50.6 L g −1 and 4.95 mg g −1, respectively at 10 mg L −1 concentration with significant reusability. The material showed significant antibacterial activity against Escherichia coli and Staphylococcus aureus . Graphical abstract: Image 1 Highlights: Ag/Ag2 O/ZrO2 /GL was prepared by incorporating Ag and Zr into guajava framework. Ag/Ag2 O/ZrO2 /GL was investigated for adsorption and antibacterial applications. Its potential as adsorbent was accounted through the partition coefficient. Schematic mechanism of adsorption of Methylene blue is given herein. Application of Ag/Ag2 O/ZrO2 /GL is found as efficient technology for water treatment.